The Public Perception of Public Transportation in Malaysia - Santuri, Teddy Pelangi; Baharom, Nur Atiqah Binti (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
The purpose of this study was to analyze public perceptions of public transportation in Malaysia. The type of research used is qualitative research. Data collection techniques are by observation, interview, and documentation, which then obtained data are analyzed using qualitative analysis. The results showed that people used various types of public transportation in Malaysia according to their daily needs. To avoid congestion, many people use trains, other than that people also often use buses, also now since the emergence of online transportation such as Grab, many people have also switched to using Grab, besides that, Taxis are usually used by people every day.